Odpowiedź :
Odpowiedź:
e) 12⁷ : 6⁷ = (12 : 6)⁷ = 2⁷
4,7³ : 10³ = (4,7 : 10)³ = 0,47³
[tex](\frac{20}{21} )^{5} :(\frac{15}{14} )^{5} =(\frac{20}{21} :\frac{15}{14} )^{5} =(\frac{20}{21} *\frac{14}{15} )^{5} =(\frac{4}{3} *\frac{2}{3})^{5}=(\frac{8}{9} )^{5}[/tex]
(-8)⁹ : (-2)⁹ = (-8 : (-2))⁹ = 4⁹
[tex](\frac{2}{3})^{7} :(-1,5)^{7}=(\frac{2}{3})^{7} :(-\frac{3}{2}) ^{7}=(\frac{2}{3} :(-\frac{3}{2}) ^{7}=(\frac{2}{3} *(-\frac{2}{3}) ^{7}=(-\frac{4}{9} )^{7}[/tex]
f) ((3²)⁵)² = 3²ˣ⁵ˣ² = 3²⁰
((0,4²)⁴)⁵ = 0,4²ˣ⁴ˣ⁵ = 0,4⁴⁰
[tex](((\frac{7}{8} )^{3} )^{4} )^{2} = (\frac{7}{8} )^{3*4*2} =(\frac{7}{8} )^{24}[/tex]
(((-2)³)²)³ = (-2)³ˣ²ˣ³ = (-2)¹⁸
[tex](((-1\frac{1}{3} )^{2} )^{3})^{4} =(-1\frac{1}{3} )^{2*3*4} =(-1\frac{1}{3} )^{24}[/tex]